Hygienic practice during complementary feeding and associated factors among mothers of children aged 6–24 months in Borecha Woreda, southwestern Ethiopia: a community-based cross-sectional study - Birdida, Rabira Tariku; Malka, Erean Shigign; Negash Kush, Efrem; Tolesa Alemu, Fikadu (Frontiers in Pediatrics, 2024)
Introduction: Complementary feeding is a critical time of transition in the life of infant and complementary foods should be hygienically prepared, stored and fed with clean hands, dishes and utensils to prevent diseases. However, Prevalence and risk factors of hygienic complementary feeding practice is not well addressed in Ethiopia especially in study area.Objective: To assess hygienic practices and associated factors during complementary feeding among mothers with children 6 to 24 months old in Borecha Woreda,